Past and future variability in the hydrological regime of the Koshi basin, Nepal - Bharati, Luna; Gurung, Pabitra; Bhattarai, Utsav (Informa UK Limited, 2016)
Planning adaptation strategies in response to climate change (CC) can be a daunting task, especially in regions such as the Koshi Basin in the Himalayas; where CC impacts are still uncertain. This paper recommends targeting adaptation strategies by focusing on changes in variability between the past and future climates at smaller scales. The Soil and Water Assessment Tool (SWAT) and the Indicators of Hydrologic Alteration (IHA) are used for analysis. Results show: (i) higher maximum precipitation during monsoon and post-monsoon, and lower maximum precipitation during winter; (ii) increase in precipitation and flows in the trans mountain region during all seasons, except for flows during monsoon; (iii) increase in post-monsoon precipitation and routed flow volumes; (iv) decrease in precipitation during winter and routed flow volumes in all the regions, except the trans mountain region; and (v) increase in frequency of high peak flows and decrease in baseflows.